(untitled) (Global Journal of Human-Social Science, 2020)
This paper analyzes the conception of the cyber-self, online identity and educational activity in a group of Taiwanese and Indonesian university students. In this work, pupil commentary is focused on, rather than statistical findings, as it is believed that such numerical data may not be entirely reliable and/or consistent. Areas investigated include research and study; entertainment, video and games; music and arts; communicating with others (local and international); "trolling" or investigating others; social networks; news; shopping and banking; and other personal activities. These areas and student identities were all studied. How the online self is being used to supplement offline identity was an important area of research. Another important area was the conception of "real" versus "not real" activity and behavior in on-and offline communication. Students view of themselves in both positive and negative ways is looked at. Human agency and the degree to which individuals shape, or are shaped by the structures and constraints of the virtual world are studied.